The Healthcare Value Chain Demystifying the Role of GPOs and PBMs - Burns, Lawton Robert (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This volume analyzes group purchasing organizations (GPOs) and pharmacy benefit managers (PBMs) in order to better understand the significant roles that these entities play in the healthcare supply chain. It examines who they contract with, on what terms, and who they represent and answer to while charting their historical development. The analysis reveals that the current roles of both players have historical roots that explain why they behave the way they do. Finally, the book reviews the evidence base on the performance results of these two players. This work fills a void in our understanding about two important and controversial players in the healthcare value chain. Both organizations are cloaked in secrecy - partly by virtue of the private sector contracts they negotiate, partly by virtue of the lack of academic attention. Both play potentially important roles in controlling healthcare costs, albeit using contracting strategies and reimbursement mechanisms that arouse suspicion among stakeholders. This timely text explicates how these organizations arose and evolved to shed more light on how they really operate. Lawton Robert Burns is the James Joo-Jin Kim Professor at the Wharton School of the University of Pennsylvania, USA and Professor in the Departments of (a) Health Care Management and (b) Management. He is also past Director of the Wharton Center for Health Management & Economics, and since 2013, Co-Director of the Life Sciences and Management Program (LSMP) at the University of Pennsylvania. From 2007-2014, he served as Chair of the Health Care Management Department. .
Chapter 1: Introduction to the value chain -- Chapter 2: Introduction to the intermediaries in the healthcare value chain -- Chapter 3: Overview of GPOs -- Chapter 4: History of GPOs (co-authored with David Cassak) -- Chapter 5: Performance of GPOs -- Chapter 6: Analysis of Specific GPO Issues -- Chapter 7: Overview of PBMs -- Chapter 8: History of PBMs -- Chapter 9: Performance of PBMs -- Chapter 10: Analysis of Specific PBM Issues.
Keywords: Health services administration; Business logistics; Production management; Health Care Management; Supply Chain Management; Operations Management